Pengaruh Kualitas Informasi dan Brand Image Terhadap Minat Beli Konsumen pada Produk iPhone Second di Semarang dengan Persepsi Konsumen sebagai Variabel Intervening (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2025)
This study explores the impact of information quality and brand image on the purchase intention of consumers buying second-hand iPhones, considering consumer perception as an intervening variable. A total of 385 respondents who bought second-hand iPhones at PS Store Semarang participated in the research. The results show that brand image positively influences purchase intention, with a path coefficient of 0.116 and a p-value of 0.024. Brand image also significantly affects consumer perception, with a path coefficient of 0.339 and a p-value of 0.000. Conversely, information quality does not have a direct significant impact on purchase intention (path coefficient of 0.123, p-value of 0.099). However, it significantly affects consumer perception (path coefficient of 0.634, p-value of 0.000). Consumer perception significantly influences purchase intention, with a path coefficient of 0.723 and a p-value of 0.000. It serves as a crucial mediator between brand image and purchase intention (indirect effect of 0.245, p-value of 0.000) and between information quality and purchase intention (indirect effect of 0.458, p-value of 0.000). The model accounts for 89.8% of the variance in purchase intention and 91.0% in consumer perception, highlighting the importance of enhancing information quality and maintaining a strong brand image to boost consumer purchase intentions.